A Bidirectional Mendelian Randomization Study of Selenium Levels and Ischemic Stroke - Fang, Hui; Liu, Weishi; Zhang, Luyang; Pei, Lulu; Gao, Yuan; Zhao, Lu; Zhang, Rui; Yang, Jing; Song, Bo; Xu, Yuming (Frontiers in Genetics, 2022)
Background: Previous observational studies have shown that circulating selenium levels are inversely associated with ischemic stroke (IS). Our aims were to evaluate the causal links between selenium levels and IS, and its subtypes by Mendelian randomization (MR) analysis. Methods: We used the two-sample Mendelian randomization (MR) method to determine whether the circulating selenium levels are causally associated with the risk of stroke. We extracted the genetic variants (SNPs) associated with blood and toenail selenium levels from a large genome-wide association study (GWAS) meta-analysis. Inverse variance weighted (IVW) method was used as the determinants of the causal effects of exposures on outcomes. Results: A total of 4 SNPs (rs921943, rs6859667, rs6586282, and rs1789953) significantly associated with selenium levels were obtained. The results indicated no causal effects of selenium levels on ischemic stroke by MR analysis (OR = 0.968, 95% CI 0.914-1.026, p = 0.269). Meanwhile, there was no evidence of a causal link between circulating selenium levels and subtypes of IS. Conclusion: The MR study indicated no evidence to support the causal links between genetically predicted selenium levels and IS. Our results also did not support the use of selenium supplementation for IS prevention at the genetic level.